Regulatory capital: Implications on credit creation and profitability - Isaiah Oino (Cogent Economics & Finance, 2021)
The level of liquidity in banking determines the extent to which a bank can meet its financial intermediation role. Liquidity and regulatory capital requirements have gained momentum after the 2008 global financial crisis. Meeting the shareholder's need (i.e profitability) and regulatory requirements (liquidity and capital) is a delicate balance that banks strive to achieve. Applying a pooled fixed-effects model on a complete panel of 179 banks from 2008 to 2019 in the European Union, the results show how banks in Europe strive to achieve profitability requirements at the same time meeting the regulatory hurdles. The results indicate, better-capitalised banks lend much more, which in turn enhances profitability. Also, the findings indicate that higher capital requirements for banks significantly positively influence liquidity. Furthermore, there is an inverse relationship between growth in loans and total regulatory capital. The results imply banks should ensure that the quality of the capital base and the buffers above the regulatory minimum are built up during periods of strong earnings growth. The results also indicate that profitability is significant in influencing the liquidity of the bank. The results emphasise the need to regulate not only the minimum capital requirement but also the liquidity level.
Keywords: 330; assets; capital; Liquidity; profitability; requirements